KONTRIBUSI KOPERASI DALAM PENYERAPAN TENAGA KERJA DI INDONESIA - Azhari Azhari; Azhari Azhari (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2020)
The purpose of study to descriptively evaluate the existence and role of cooperatives in employment in Indonesia. This study uses descriptive analysis. The number of cooperatives in Indonesia reaches 212,135 units with a total membership of 15% of the total population of Indonesia. As many as 30% of cooperatives in Indonesia are inactive for various reasons. The level of employment in the cooperative sector is only able to absorb 0,5% of the entire Indonesian population who work. Some suggestions that can be done include; (1) Increase the participation of cooperative members; (2) Providing a conducive climate for cooperatives, access to finance and business development; (3) Improving counseling and training for managers, supervisors and apparatus of cooperating supervisors; and (4) Encouraging Micro, Small and Medium Enterprises (MSMEs) to establish secondary cooperatives.Keywords: Cooperative, capital, SHU, labor.